Socioeconomic aspects of riparian vegetation debt in the state of Sao Paulo, Brasil - Murakami, Lia Yukari K. [UNESP]; Massi, Klécia Gili [UNESP]; Mendes, Tatiana Sussel G. [UNESP] (Elsevier, 2023)
Most of Brazilian's remaining native vegetation occurs inside private properties. Therefore, the effectiveness of environmental policies is affected by landowner's decisions. Brazilian Native Vegetation Protection Law delimits riparian permanent preservation areas (RPA) defined according to stream and river widths. Restoration legal needs (the environmental debt or liability) can increase native cover in Brazil. However, costly ecological restoration may prevent small owners from doing that. For that matter, it is important to understand and know the socioeconomic variables behind the restoration debt in certain areas in Brazil. Thus, we aimed at analyzing distribution of environmental debt in these RPA and related it to the socio- economic condition of the municipalities. We found that most of Sao Paulo state has environmental debt within its RPA. High environmental debt in Sao Paulo state is associated with the agricultural sector. Some of these regions are wealth and restoration by total planting might be well applied for compliance with legislation. In other places, where environmental debt and poverty are high, assisted natural regeneration might be an efficient technique, along with agroforestry systems. Some regions where low environmental debt coincided with poverty, environmental compensation could play an important role in a policy mix for socially equitable conservation and restoration.
Keywords: Agriculture; Compliance; Forest code; Legislation; Poverty; Restoration